THE RELATIONSHIP BETWEEN THE LEVEL OF METACOGNITIVE SKILLS AND THE LEVEL OF PERFORMANCE IN SOLVING MATHEMATICAL PROBLEMS AMONG FORM FOUR STUDENTS - Mohamad Amir Farhan Roslan; Nur Hamiza Adenan; Siew Wei Tho; Zhaofeng Zeng (Program Studi S1 Pendidikan Matematika FKIP Universitas Bengkulu, 2025)
This study aims to identify the relationship between the level of metacognitive skills and the performance of form four students in solving mathematical problems at Sekolah Menengah Kebangsaan Keratong, Bandar Tun Razak, Pahang. This correlational study involves 33 students from three classes selected as the study sample using convenience sampling techniques. Data were collected through questionnaires and a mathematical problem-solving test, then analyzed using descriptive and Pearson correlation statistical methods. The instruments used demonstrated a high level of validity, with a Content Validity Index (CVI) of 1.00 as assessed by four experts. Additionally, a pilot study showed that the instruments had high reliability, as evidenced by Cronbach’s Alpha value of 0.89. The analysis revealed that students' overall metacognitive skill levels were high (M = 2.99, SD = 0.67). However, students' performance in solving mathematical problems was very low, with an average score of 34.47%. The findings also indicated a moderate and significant relationship between students’ metacognitive skill levels and their performance in solving mathematical problems (r = 0.43, p < 0.05). In conclusion, students with higher metacognitive skills tend to perform better in solving mathematical problems. The study highlights the need to incorporate metacognitive elements comprehensively into the mathematics curriculum to improve student performance, particularly in Mathematics.